Exploring the Influence of Coal Rubble and Pine Bark Substrate Mixes on Germination, Spiral Rooting, Substrate Chemical and Physical Properties: Using Tobacco as Test Crop - Mazarura , Upenyu (Asian Journal of Agriculture and Rural Development, 2013)
A study was carried out under greenhouse conditions to establish the role of substrate physical and chemical properties. Pine bark and coal rubble were mixed at 100, 75, 50, 25, and 0% by volume. A farmers’ standard practice (50% pine bark + 50% sand) was included as a control. The experiment was made up of three blocks and six treatments arranged in a randomized complete block design. The particle density of the substrates in this study was virtually the same. The bulk density, total porosity, and aeration porosity, however, were highest with 100% coal rubble and decreased with decreasing coal rubble proportion while water holding porosity increased with decreasing coal proportion. Germination decreased with increasing coal rubble at 14 to 28 and at 35 days after sowing (DAS). A mix of between 0 to 50% coal rubble with pine bark seemed ideal for germination. Aeration porosity, total porosity, and bulk density were negatively correlated to germination (14 to 28 DAS) while water holding porosity was positively correlated. Overall, the best germination was for 0 to 50 % coal rubble with subsequent bulky density of 0.46 to 0.83, total porosity 71 to 63%, aeration porosity 21 to 35% and water holding porosity 49 to 31% respectively. However, the measured total porosity and water holding porosity of the standard substrate (50%S0%CR50%PB) used normally by farmers were below the expected range, while the aeration porosity was on the low end. This makes this mix prone to aeration problems. The pH of the float water decreased with increase in time from sowing and proportion of coal in the mix while EC was not affected.